Increasing stress resilience in older adults through a 6-week prevention program: effects on coping strategies, anxiety symptoms, and cortisol levels - Richer, Marie-Josée; Grenier, Sébastien; Lupien, Sonia; Plusquellec, Pierrich (Frontiers in Psychology, 2025)
IntroductionAs people age, chronic stress, resulting in prolonged or repeated activation of the hypothalamic–pituitary–adrenal (HPA) axis, has been associated with long-term adverse health outcomes. Coping strategies and social support have been recognized as contributing to resilience to stress in older adults. Few studies have evaluated stress management training (SMT) interventions based on psychoneuroendocrinology that were designed to be delivered to healthy older adults in community settings.MethodsIn this study, a total of 170 older adults (mean age = 76.07, SD = 7.67) participated in a cluster-randomized trial designed to compare the delivery of an SMT intervention with a waitlist condition.ResultsThe effect of SMT on coping strategies, stress, anxiety, and depression was measured 3 weeks and 3 months after the intervention. In addition, we tested the effect on basal cortisol secretion over 2 days from saliva samples upon awakening and the total diurnal cortisol output [area under the curve with respect to ground (AUCg)]. Results from repeated measures analyses of variance showed that participants who received the intervention demonstrated a significant increase in problem-solving coping strategies and a decrease in anxiety scores 3 weeks after the intervention compared to the waitlist group. STM participants also demonstrated lower cortisol levels on the AUCg index. At the 3-month follow-up, gains were maintained only on the AUCg index.DiscussionThis type of brief preventive program could reduce basal cortisol levels in older adults, which may be an important protective factor against health outcomes associated with chronic HPA activation. Our results provide sufficient evidence to warrant further research to improve the effectiveness of O’stress in different settings.